Effects of luteinizing hormone-releasing hormone and arginine-vasotocin on the sperm-release response of Günther's Toadlet, Pseudophryne guentheri - Silla Aimee J (BMC, 2010)
Abstract Background Luteinizing hormone-releasing hormone (LHRH) is an exogenous hormone commonly used to induce spermiation in anuran amphibians. Over the past few decades, the LHRH dose administered to individuals and the frequency of injection has been highly variable. The sperm-release responses reported have been correspondingly diverse, highlighting a need to quantify dose-response relationships on a species-specific basis. This study on the Australian anuran Pseudophryne guentheri first evaluated the spermiation response of males administered one of five LHRHa doses, and second, determined whether AVT administered in combination with the optimal LHRHa dose improved sperm-release. Methods Male toadlets were administered a single dose of 0, 1, 2, 4 or 8 micrograms/g body weight of LHRHa. A 4 micrograms/g dose of AVT was administered alone or in combination with 2 micrograms/g LHRHa. Spermiation responses were evaluated at 3, 7 and 12 h post hormone administration (PA), and sperm number and viability were quantified using fluorescent microscopy. Results LHRHa administration was highly effective at inducing spermiation in P. guentheri, with 100% of hormone-treated males producing sperm during the experimental period. The number of sperm released in response to 2 micrograms/g LHRHa was greater than all other doses administered and sperm viability was highest in the 1 microgram/g treatment. The administration of AVT alone or in combination with LHRHa resulted in the release of significantly lower sperm numbers. Conclusion Overall, results from this study suggest that in P. guentheri, LHRHa is effective at inducing spermiation, but that AVT inhibits sperm-release.